The homeless use Facebook?! Similarities of social network use between college students and homeless young adults - Guadagno, Rosanna E.; Muscanell, Nicole L.; Pollio, David E. (Computers in human behavior, 2013)
► We compared technology use among homeless young adults with college students. ► Social network site (SNS) usage was assessed. ► Technology use was strikingly similar. ► This calls for a paradigm shift in researchers’ understanding of technology use. ► And suggests that contemporary young adults are far more similar than prior research would suggest. This research compared technology use among homeless young adults with that of college students as a means of understanding technology use among young adults today; people who have grown up with technology. Specifically, social network site (SNS) usage was assessed for two age-matched young adult samples, one drawn from a large introductory psychology subject pool, and a second from homeless young adults who were approached for participation when they entered metropolitan shelters. Overall, technology use was strikingly similar. These results call for a paradigm shift in researchers’ understanding of technology use and indicate that contemporary young adults sampled across socio-economic class and varying ethnicities are far more similar than prior research would suggest. These results call into question whether the term “digital divide” is useful for describing group differences in technology use as our results suggest the divide has narrowed considerably.